2013
DOI: 10.1590/s0036-46652013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Renal Histopathological Findings in Dogs With Visceral Leishmaniasis

Abstract: Visceral leishmaniasis affects various organs including the kidneys; which can lead to renal failure and death. In order to verify this renal involvement, material was evaluated from 100 dogs naturally infected and with serological diagnosis of canine visceral leishmaniasis (CVL). Inflammatory changes were present in 25.3% of the tubules, in 67.0% of interstitium and in 52.0% of glomeruli. There was no significant difference (p > 0.05) between the presence of glomerulonephritis in symptomatic and oligosymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…A study carried out with 55 CVL‐positive dogs in Brazil, reported mesangial proliferative glomerulonephritis as the most common finding, affecting 32.7% of the dogs (Costa et al, ). The findings agree with those from other studies, indicating that renal damage is common in leishmaniasis (Rigo et al, ).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…A study carried out with 55 CVL‐positive dogs in Brazil, reported mesangial proliferative glomerulonephritis as the most common finding, affecting 32.7% of the dogs (Costa et al, ). The findings agree with those from other studies, indicating that renal damage is common in leishmaniasis (Rigo et al, ).…”
Section: Introductionsupporting
confidence: 93%
“…Although many animals have no perceptible clinical changes, the kidneys are usually affected by injuries caused by visceral leishmaniasis (Rigo et al, ). Thus, glomerulonephritis constitutes one of the major causes of death in dogs positive for CVL (Kerns et al, ; Pickering et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Membranoproliferative glomerulonephritis was the most frequently observed and was present in 59% of the dogs, a higher value than the 30% observed by Costa et al (2003) and 18% observed by Rigo et al (2013). Glomerular fibrosis was identified in 45.5% of the dogs and also described by other authors (ZATELLI et al, 2003).…”
Section: Discussionmentioning
confidence: 49%
“…Fibrosis is most likely related to a more chronic stage of CKD (NEWMAN et al, 2009), which explains its occurrence mainly in dogs with uremic syndrome (P=0,045, Mann-Whitney test). Membranous glomerulonephritis was present in 34.4% of the dogs and was also described by Zatelli et al (2003) and Rigo et al (2013), but it was not identified in the studies of Costa et al (2003). It occurs by the deposition of immune complexes on the subepithelial surface of the glomerular basement membrane (SERAKIDES, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, therapy with amphotericin B deoxycholate reduces serum antibody levels and parasite loads and increases the lymphoproliferative response, but the effects are transitory (78). In addition, renal failure is a common outcome (79), and the drug is not recommended for canine therapy. Treatment with liposomal amphotericin B resulted in recovery in dogs, but despite the initial effectiveness, relapses can occur (78, 80).…”
Section: Amphotericin B Deoxycholate and Liposomal Amphotericin Bmentioning
confidence: 99%